2005
DOI: 10.3171/jns.2005.102.1.0068
|View full text |Cite
|
Sign up to set email alerts
|

Influence of endothelial nitric oxide synthase T-786C single nucleotide polymorphism on aneurysm size

Abstract: The eNOS T-786C SNP genotype does not influence the size of aneurysms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 10 publications
5
18
3
Order By: Relevance
“…32 In contrast, some recent studies on the polymorphism of eNOS have failed to demonstrate the positive relation with CA formation or rupture. 33 These results may suggest that the dysfunction of eNOS can be compensated for with nNOS upregulation in cerebral arteries unlike in the aorta and further strengthen the hypothesis that there is a functional difference in NOS regulation.…”
Section: Discussionsupporting
confidence: 64%
“…32 In contrast, some recent studies on the polymorphism of eNOS have failed to demonstrate the positive relation with CA formation or rupture. 33 These results may suggest that the dysfunction of eNOS can be compensated for with nNOS upregulation in cerebral arteries unlike in the aorta and further strengthen the hypothesis that there is a functional difference in NOS regulation.…”
Section: Discussionsupporting
confidence: 64%
“…On the other hand, Krischek et al 19 reported no relationship between eNOS polymorphisms and rupture of a cerebral aneurysm in Japanese patients. Moreover, Akagawa et al 1 reported the same findings of negative association between the T786C polymorphism of the eNOS gene and the formation of an intracranial aneurysm.…”
Section: Discussionsupporting
confidence: 56%
“…The outcome was similar to the previously reported findings in control populations. 1,16 There were no racial differences in the eNOS gene polymorphism distributions in similar races, such as Korean and Japanese patients. However, there were racial differences in different races, such as Korean and American or Korean and German patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study group concluded that a polymorphism of the eNOS gene correlates with the aneurysm's size, observed in Caucasian patients (Khurana et al 2003). But this could not be replicated in a study using DNA samples of Japanese patients (Akagawa et al 2005). It was also reported that three polymorphisms of this gene make it possible to single out patients with IAs that are more prone to rupture, comparing 58 ruptured to 49 unruptured IA cases of Caucasian origin (Khurana et al 2005).…”
Section: Candidate Gene Analysismentioning
confidence: 95%